1997
DOI: 10.1254/jjp.74.253
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of YM9OK, an AMPA-Receptor Antagonist,against Delayed Neuronal Death Induced by Transient Global Cerebral Ischemia in Gerbils and Rats.

Abstract: ABSTRACT-We investigated the neuroprotective effect of the ƒ¿-amino-3-hydroxy-5-methylisoxazole-4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Experimental studies bolster the idea that neuronal excitotoxicity can involve the activation of AMPA‐ and KA‐type glutamate receptors (Chen et al, 1995; Nakai et al, 2000; Moldrich et al, 2000; Hermann et al, 2001). The AMPA/KA receptor antagonist 6‐nitro‐7‐sulfamoyl‐(f)‐quinoxaline‐2, 3‐dione (NBQX) and some of its derivatives have shown protective effects against CNS damage induced by either transient global ischemia (Buchan et al, 1991; Diemer et al, 1992; Sheardown et al, 1993; Kawasaki‐Yatsugi et al, 1997; Turski et al, 1998; O'Neill et al, 2000) or traumatic injury (Wrathall et al, 1997; Rosenberg et al, 1999). Previous studies have also described the effect of KA on neurons in culture (Cox et al, 1990; Kato et al, 1991; Resink et al, 1994; Fryer et al, 1999; Ha et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies bolster the idea that neuronal excitotoxicity can involve the activation of AMPA‐ and KA‐type glutamate receptors (Chen et al, 1995; Nakai et al, 2000; Moldrich et al, 2000; Hermann et al, 2001). The AMPA/KA receptor antagonist 6‐nitro‐7‐sulfamoyl‐(f)‐quinoxaline‐2, 3‐dione (NBQX) and some of its derivatives have shown protective effects against CNS damage induced by either transient global ischemia (Buchan et al, 1991; Diemer et al, 1992; Sheardown et al, 1993; Kawasaki‐Yatsugi et al, 1997; Turski et al, 1998; O'Neill et al, 2000) or traumatic injury (Wrathall et al, 1997; Rosenberg et al, 1999). Previous studies have also described the effect of KA on neurons in culture (Cox et al, 1990; Kato et al, 1991; Resink et al, 1994; Fryer et al, 1999; Ha et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect of theanine on the AMPA receptor is 10-fold higher than its inhibitory effect on the NMDA receptor. AMPA receptor antagonists provide protection against ischemia induced by middle cerebral artery (MCA) occlusion in rats (Xue et al, 1994;Umemura et al, 1997;Kawasaki-Yatsugi et al, 1998) and forebrain ischemia in gerbils and rats (Sheardown et al, 1993;Kawasaki-Yatsugi et al, 1997). It was previously reported that twice-repeated ischemia, but not single ischemia, impaired spatial memory in rats and caused neuronal cell death characterized by an increase in the number of apoptotic cells in the hippocampal CA1 field (Iwasaki et al, 2004).…”
Section: Animalsmentioning
confidence: 99%
“…Global cerebral ischaemia causes delayed neuronal loss leading to impaired learning and memory. Both the quinoxaline and 2,3‐benzodiazepine type AMPA antagonists rescued a large fraction of pyramidal cells in the CA1 area of the hippocampus after BCO in the gerbil and after four‐vessel occlusion (4VO) in the rat (Kawasaki‐Yatsugi et al , 1997; Gyertyán et al , 1999; Nielsen et al , 1999; Kapus et al , 2004). Non‐competitive AMPA antagonists decreased hypermotility and increased spontaneous alternation response, a measure of spatial memory, after global cerebral ischaemia in gerbils (Gyertyán et al , 1999; Kapus et al , 2004).…”
Section: Discussionmentioning
confidence: 99%